Post-reform setbacks in rural employment: issue that need further scrutiny - Chadha G.K.; Sahu, P.P. (2002)
This paper looks at the pace and pattern of employment growth in the 1990s (post-reforms period) and compares it with the 1980s (pre-reforms period), based on NSS data, and attempts to figure out the challenges and threats that lie ahead for rural workers in India. The empirical evidence calls into question and optimism of pro-reform analysts on the all-round positive impact of economic reform on employment. The study also raises a number of questions that need further analysis to enable us to understand better the continuing and likely impact of the economic reforms. - Reproduced.
Keywords: Employment